Nikah Dini Bukan Pilihan (Say No To Nikah Dini Raih Impian Dulu) Bersama Masyarakat Jorong Pemukiman Baru Ii Kecamatan Koto BalingkaKabupaten Pasaman Barat - Aisyaturridho; Lailatul Jannah (Karsa : Jurnal Pengabdian Masyarakat, 2025)
The age of early marriage (under 19 years) often occurs in Jorong Pemukiman Baru 2. This figure is 7% lower than the previous 2 years. Early marriage often occurs due to social ef ects, apart from that, the content which contains quite a few adult shows also has a big influence on the mindset of children who do not get enough supervision from their parents when playing with gadgets. The impact of early marriage includes a high risk of death for young mothers. experiencing baby blues (excessive depression after giving birth), unstable economic conditions due to constraints in education and failure to achieve a future career, divorce, poor morals in society due to being an example for young people and often used as a trend, rights being taken away -Children's rights, abandonment by parents is one of the impacts of divorce. The aim of this research is, apart from carrying out  the Work Program during the KKN period, it is also to provide a wider understanding to the community, especially the people of Jorong Pemukiman Baru 2 regarding the importance of preventing early marriage, as well as strategies that can be implemented to avoid early marriage, considering the many risks posed, and the impact on oneself, family and society. Education to prevent early marriage was carried out, by Jorong, the Integrated Service Post Community Institution, POLINDES midwives, and BKB